2015
DOI: 10.12691/rpbs-3-1-3
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Evidence of the Italian Anxiety Sensitivity Index-3 (ASI-3) in Patients with Anxiety Disorders and Psychosis

Abstract: The Anxiety Sensitivity Index-3 (ASI-3) is an 18-item measure, recently developed to assess AS, based, consisting of Physical Concerns (eg, the belief that palpitations lead to a cardiac arrest), Social Concerns (eg, the belief that publicly observable anxiety reactions will elicit social refusal), and Cognitive Concerns (eg, the belief that cognitive difficulties lead to insanity). In the Italian context there is a lack of a validated measure of AS, to date.The current study assessed factor structure, reliabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 34 publications
2
7
0
4
Order By: Relevance
“…Mean scores, standard deviations, ranges, skewness, kurtosis, and Cronbach's alphas for each measure are presented in Table . The sample mean scores on all measures fell within the normal range reported in other Italian clinical samples (e.g., Bottesi et al, ; Pozza & Dèttore, ). Internal consistency estimates for all measures were good or better (Cronbach's alphas ≥ .77).…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Mean scores, standard deviations, ranges, skewness, kurtosis, and Cronbach's alphas for each measure are presented in Table . The sample mean scores on all measures fell within the normal range reported in other Italian clinical samples (e.g., Bottesi et al, ; Pozza & Dèttore, ). Internal consistency estimates for all measures were good or better (Cronbach's alphas ≥ .77).…”
Section: Resultssupporting
confidence: 74%
“…Statement choices are scored from 0 ( very little ) to 4 ( very much ). The original ASI‐3 (Taylor et al, ) has shown good psychometric properties, and its Italian version has shown good internal consistency ( α > .77 for all subscales), adequate temporal stability (ICC > .75 for all scales), and good construct validity (Ghisi et al, ; Pozza & Dèttore, ).…”
Section: Methodsmentioning
confidence: 99%
“…Luzon ve arkadaşları. psikoz tanılı hastalarda ADİ-3'ün fiziksel alt boyutunun sağlıklı kişilere göre anlamlı yüksek olduğunu 18 , Pozza ve Dettore ise düşük olduğunu saptamıştır 32 . Çalışmamızda şizofreni tanılı grupta ADİ-3 fiziksel alt boyutu kontrol grubuna göre anlamlı yüksek saptanmıştır.…”
Section: Introductionunclassified
“…Sosyal alt boyutun sosyal fobi 14,30,31 , depresif bozukluk ve yaygın anksiyete bozukluğu 33 ile ilişkisi gösterilmiştir 29 . Psikotik bozuklukta anksiyete duyarlılığının sosyal alt boyutunun sağlıklı kişiler ile benzer ya da yüksek olduğu çalışma sonuçları bulunmaktadır 18,32 . Psikotik bozukluk tanılı hastalara anksiyete bozuklukları özellikle de sosyal anksiyete bozukluğu sıklıkla eşlik etmektedir 34 .…”
Section: Introductionunclassified
See 1 more Smart Citation